Heat-resistant polylactic acid composite material and preparation method thereof
By blending polyamide 66 with polylactic acid and adding carbon fiber and nano silica, the problem of insufficient heat resistance of polylactic acid was solved, and the heat resistance and weather resistance were improved. The crystallinity and mechanical properties of the material were also improved.
Patent Information
- Application Number
- CN202511187823.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-07
AI Technical Summary
Polylactic acid has low heat resistance, which limits its application scenarios.
By blending polyamide 66 with polylactic acid and adding carbon fibers and nano-silica, the carbon fiber surface is grafted with PAMAM to enhance the interaction and promote uniform nucleation, and the nano-silica improves thermal stability, a heat-resistant polylactic acid composite material is formed after blending.
It significantly improves the heat resistance and weather resistance of composite materials, reduces phase separation, and enhances the crystallinity and mechanical properties of the materials.
Smart Images

Figure BDA0005562779060000081 
Figure BDA0005562779060000091 
Figure BDA0005562779060000101
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of polylactic acid, in particular, to a heat-resistant polylactic acid composite material and a preparation method thereof. BACKGROUND
[0002] Polylactic acid is a biodegradable plastic made of renewable resources such as corn starch, sugarcane, etc. Fermented lactic acid as raw material, through polymerization reaction. It is widely used in packaging, textile, medicine and other fields because of its good processing performance, biocompatibility and complete degradability. However, the heat resistance of polylactic acid is low, which greatly limits its application scenarios. SUMMARY
[0003] The purpose of the present application is to provide a heat-resistant polylactic acid composite material and a preparation method thereof, which solves the problem of poor heat resistance of existing polylactic acid.
[0004] The embodiments of the present application are implemented by the following technical solutions:
[0005] A heat-resistant polylactic acid composite material, comprising, by weight: polylactic acid 80-100 parts, polyamide 66 20-50 parts, carbon fiber 10-30 parts, and nano-silicon dioxide 5-15 parts.
[0006] The polylactic acid comprises 30wt%-40wt% of L-type polylactic acid and the balance of D-type polylactic acid.
[0007] Polylactic acid is a biodegradable material, but its heat resistance is low, which greatly limits its application field. The common polylactic acid modification at present is mainly physical blending modification and chemical modification of molecular chain modification, among which, chemical modification is more suitable for laboratory, and the applicant hopes to improve the heat resistance of polylactic acid through physical blending modification.
[0008] The application selects polyamide 66 and polylactic acid for blending, the polyamide 66 has good thermal stability and mechanical properties, and can improve the heat resistance of the composite material, but the compatibility between the polyamide 66 and the polylactic acid is poor, and phase separation is prone to occur, especially after long-term use and aging, and the performance is greatly reduced. Therefore, the application additionally adds carbon fibers and nano silicon dioxide, wherein the carbon fibers can further improve the heat resistance of the composite material, and also can reduce the phase separation. The carbon fibers usually have certain active functional groups on the surface, such as hydroxyl and carboxyl groups, and the functional groups can have physical or chemical interaction with the polymer matrix, and enhance the adhesion between the fibers and the matrix. The strong interaction helps to bind the different phases more closely together, and reduces the phase separation. The carbon fibers can act as heterogeneous nucleation points, and promote uniform nucleation in the polymer crystallization process. This not only can improve the crystallinity of the composite material, but also can make the crystallization more uniform, thereby helping to reduce the phase separation caused by uneven crystallization. The presence of the fibers can also limit the mobility of the polymer chain segments, reduce the possibility of molecular rearrangement, and further inhibit the phase separation. In addition to improving the thermal stability of the composite material, the nano silicon dioxide can also improve the weather resistance of the composite material, and further reduce the performance loss of the composite material during use.
[0009] Preferably, the surface of the carbon fiber is grafted with PAMAM.
[0010] In order to enhance the bonding degree between the carbon fiber and the matrix, the application adopts the carbon fiber after surface modification.
[0011] Preferably, the mass ratio of PAMAM to carbon fiber is 1:(3-8).
[0012] Preferably, the length of the carbon fiber is 1mm-3mm.
[0013] Preferably, the polyamide comprises: a first component with an average molecular weight of 2000-4000, a second component with an average molecular weight of 6000-8000, and a third component with an average molecular weight of 12000-16000.
[0014] The first component, the second component and the third component are all polyamides.
[0015] Preferably, the mass ratio of the first component to the second component is 1:(2-4); and the mass ratio of the first component to the third component is 3:(5-9).
[0016] Preferably, the preparation method of the heat-resistant polylactic acid composite material comprises: melting and blending polylactic acid, polyamide 66, carbon fibers and nano silicon dioxide to obtain a heat-resistant polylactic acid composite material; the blending temperature is 240-300 DEG C, and the blending time is 8-15h.
[0017] Preferably, the modification method of the carbon fiber comprises: after dissolving the PAMAM in the methanol solution, putting the coupling agent and the carbon fiber, reacting at 80-240 DEG C for 5-8 hours, and obtaining the modified carbon fiber.
[0018] Preferably, the modification method of the carbon fiber comprises: after dissolving the PAMAM in the methanol solution, putting the coupling agent and the carbon fiber, reacting at 80-120 DEG C for 1-3 hours, then increasing the temperature to 180-240 DEG C, and keeping the temperature for 4-5 hours, and finally obtaining the modified carbon fiber.
[0019] Preferably, the heating rate is 10-20 DEG C / min.
[0020] The present application has at least the following beneficial effects:
[0021] The present application selects polyamide 66 and polylactic acid to be blended, polyamide 66 has good thermal stability and mechanical properties, and can improve the heat resistance of the composite material, but the compatibility between polyamide 66 and polylactic acid is poor, and phase separation is prone to occur, especially after long-term use and aging, phase separation is more prone to occur, resulting in a significant reduction in performance. Therefore, the present application additionally adds carbon fiber and nano-silicon dioxide, wherein the carbon fiber can further improve the heat resistance of the composite material, and also can reduce phase separation. The surface of the carbon fiber usually has certain active functional groups, such as hydroxyl and carboxyl groups, which can physically or chemically interact with the polymer matrix, and enhance the adhesion between the fiber and the matrix. This strong interaction helps to bind different phases more closely together, reducing phase separation. Carbon fiber can act as a heterogeneous nucleation point, promoting uniform nucleation during the polymer crystallization process. This not only can improve the crystallinity of the composite material, but also can make the crystallization more uniform, thereby helping to reduce phase separation caused by uneven crystallization. The presence of fibers can also limit the mobility of polymer segments, reducing the possibility of molecular rearrangement, and thus inhibiting phase separation. In addition to improving the thermal stability of the composite material, nano-silicon dioxide can also improve the weather resistance of the composite material, thereby reducing the performance loss of the composite material during use. DETAILED DESCRIPTION
[0022] In order to make the purpose, method scheme and advantages of the embodiments of the present application more clear, the method scheme in the embodiments of the present application is described clearly and completely, obviously, the described embodiments are part of the embodiments of the present application, not all the embodiments.
[0023] Embodiment 1: A heat-resistant polylactic acid composite material, comprising, by weight: polylactic acid 80 parts, polyamide 66 20 parts, carbon fiber 10 parts, and nano-silicon dioxide 5 parts; the polylactic acid comprises 30 wt% of L-type polylactic acid and the balance of D-type polylactic acid; the length of the carbon fiber is 1 mm.
[0024] Embodiment 2: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 100 parts, polyamide 66 50 parts, carbon fiber 30 parts, nano-silica 15 parts; the polylactic acid comprises 40wt% L-type polylactic acid and the balance D-type polylactic acid; the length of the carbon fiber is 3mm.
[0025] Embodiment 3: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, nano-silica 10 parts; the polylactic acid comprises 35wt% L-type polylactic acid and the balance D-type polylactic acid; the length of the carbon fiber is 2mm.
[0026] Embodiment 4: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, nano-silica 10 parts; the polylactic acid comprises 35wt% L-type polylactic acid and the balance D-type polylactic acid; the length of the carbon fiber is 2mm;
[0027] the surface of the carbon fiber is grafted with PAMAM; the mass ratio of PAMAM to carbon fiber is 1:3; the polyamide comprises a first component with an average molecular weight of 2000, a second component with an average molecular weight of 6000, and a third component with an average molecular weight of 12000; the mass ratio of the first component to the second component is 1:2-; the mass ratio of the first component to the third component is 3:5;
[0028] the modification method of the carbon fiber comprises: dissolving PAMAM in a methanol solution, then adding a coupling agent and carbon fiber, reacting at 80°C for 5h-8h, and obtaining modified carbon fiber.
[0029] Embodiment 5: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, nano-silica 10 parts; the polylactic acid comprises 35wt% L-type polylactic acid and the balance D-type polylactic acid; the length of the carbon fiber is 2mm.
[0030] the surface of the carbon fiber is grafted with PAMAM; the mass ratio of PAMAM to carbon fiber is 1:8; the polyamide comprises a first component with an average molecular weight of 4000, a second component with an average molecular weight of 8000, and a third component with an average molecular weight of 16000; the mass ratio of the first component to the second component is 1:4; the mass ratio of the first component to the third component is 3:9;
[0031] the modification method of the carbon fiber comprises: dissolving PAMAM in a methanol solution, then adding a coupling agent and carbon fiber, reacting at 240°C for 5h-8h, and obtaining modified carbon fiber.
[0032] Embodiment 6: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, nano-silica 10 parts; the polylactic acid comprises: 35wt% of L-type polylactic acid and the balance of D-type polylactic acid; the length of the carbon fiber is 2mm;
[0033] the surface of the carbon fiber is grafted with PAMAM; the mass ratio of PAMAM to carbon fiber is 1:6; the polyamide comprises: a first component with an average molecular weight of 3000, a second component with an average molecular weight of 7000, and a third component with an average molecular weight of 14000; the mass ratio of the first component to the second component is 1:3; the mass ratio of the first component to the third component is 3:7;
[0034] the modification method of the carbon fiber comprises: dissolving PAMAM in a methanol solution, then adding a coupling agent and carbon fiber, reacting at 160℃ for 5-8h to obtain modified carbon fiber.
[0035] Embodiment 7: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, nano-silica 10 parts; the polylactic acid comprises: 35wt% of L-type polylactic acid and the balance of D-type polylactic acid; the length of the carbon fiber is 2mm;
[0036] the surface of the carbon fiber is grafted with PAMAM; the mass ratio of PAMAM to carbon fiber is 1:6; the polyamide comprises: a first component with an average molecular weight of 3000, a second component with an average molecular weight of 7000, and a third component with an average molecular weight of 14000; the mass ratio of the first component to the second component is 1:3; the mass ratio of the first component to the third component is 3:7;
[0037] after dissolving PAMAM in a methanol solution, adding a coupling agent and carbon fiber, incubating at 80℃ for 1h, then heating to 180℃, incubating for 4h, finally obtaining modified carbon fiber; the heating rate is 10℃ / min.
[0038] Embodiment 8: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, nano-silica 10 parts; the polylactic acid comprises: 35wt% of L-type polylactic acid and the balance of D-type polylactic acid; the length of the carbon fiber is 2mm;
[0039] The surface of the carbon fiber is grafted with PAMAM, and the mass ratio of PAMAM to the carbon fiber is 1:6; the polyamide comprises a first component with an average molecular weight of 3000, a second component with an average molecular weight of 7000, and a third component with an average molecular weight of 14000; the mass ratio of the first component to the second component is 1:3; and the mass ratio of the first component to the third component is 3:7.
[0040] After the PAMAM is dissolved in a methanol solution, the coupling agent and the carbon fiber are put in, and then the temperature is kept at 120℃ for 3h, and then the temperature is increased to 240℃ for 5h, and finally the modified carbon fiber is obtained; the temperature increasing rate is 20℃ / min.
[0041] Example 9: A heat-resistant polylactic acid composite material, comprising, in parts by weight: polylactic acid 90 parts, polyamide 66 35 parts, carbon fiber 20 parts, and nano-silicon dioxide 10 parts; the polylactic acid comprises 35wt% of L-type polylactic acid and the balance of D-type polylactic acid; and the length of the carbon fiber is 2mm.
[0042] The surface of the carbon fiber is grafted with PAMAM, and the mass ratio of PAMAM to the carbon fiber is 1:6; the polyamide comprises a first component with an average molecular weight of 3000, a second component with an average molecular weight of 7000, and a third component with an average molecular weight of 14000; the mass ratio of the first component to the second component is 1:3; and the mass ratio of the first component to the third component is 3:7.
[0043] After the PAMAM is dissolved in a methanol solution, the coupling agent and the carbon fiber are put in, and then the temperature is kept at 95℃ for 2.4h, and then the temperature is increased to 220℃ for 4.5h, and finally the modified carbon fiber is obtained; the temperature increasing rate is 15℃ / min.
[0044] Example 10: A preparation method of the heat-resistant polylactic acid composite material, comprising: melting and blending polylactic acid, polyamide 66, carbon fiber, and nano-silicon dioxide to obtain the heat-resistant polylactic acid composite material; the blending temperature is 240℃, and the blending time is 8h.
[0045] Example 11: A preparation method of the heat-resistant polylactic acid composite material, comprising: melting and blending polylactic acid, polyamide 66, carbon fiber, and nano-silicon dioxide to obtain the heat-resistant polylactic acid composite material; the blending temperature is 300℃, and the blending time is 15h.
[0046] Example 12: A preparation method of the heat-resistant polylactic acid composite material, comprising: melting and blending polylactic acid, polyamide 66, carbon fiber, and nano-silicon dioxide to obtain the heat-resistant polylactic acid composite material; the blending temperature is 260℃, and the blending time is 12h.
[0047] Comparative Example 1: The difference from Example 9 is that there is no L-type polylactic acid.
[0048] Comparative Example 2: The difference from Example 9 is that there is no D-type polylactic acid.
[0049] Comparative Example 3: The difference from Example 9 is that there is no first component in the polyamide.
[0050] Comparative Example 4: The difference from Example 9 is that there is no second component in the polyamide.
[0051] Comparative Example 5: The difference from Example 9 is that there is no third component in the polyamide.
[0052] Comparative Example 6: The difference from Example 9 is that the length of the carbon fiber is 5 mm.
[0053] Test:
[0054] Heat resistance test: The polylactic acid composite prepared according to the component ratio of Examples 1-9 and Comparative Examples 1-6 and the preparation method of Examples 10-12 is tested for heat resistance according to GB / T33047.1-2016 “Plastics-Polymer Thermogravimetry-General Principles”. The test results are shown in Table 1 (unit: ℃).
[0055] Table 1
[0056]
[0057]
[0058] From the test results of Examples 1-9, it can be seen that the polylactic acid composite prepared according to the component ratio of the heat-resistant polylactic acid composite provided by the present application and the preparation method of Examples 10-12 has good heat resistance.
[0059] From the comparison of the test results of Example 4 and Example 3, it can be seen that the composition of the polyamide and the modification of the carbon fiber can greatly improve the heat resistance of the polylactic acid composite.
[0060] From the comparison of the test results of Example 7 and Example 6, it can be seen that the temperature control in the modification method of the carbon fiber affects the heat resistance of the polylactic acid composite.
[0061] From the comparison of the test results of Examples 10-12, it can be seen that after using the preparation parameters provided in Example 12, the heat resistance of the polylactic acid composite is best.
[0062] The polylactic acid composite material prepared by the preparation method of Examples 10-12 was subjected to the aging resistance performance test, and the product was subjected to the thermal oxidation aging treatment for 144 hours, and then the product was subjected to the heat resistance test to obtain the heat resistance retention rate, the heat resistance retention rate=(decomposition temperature before aging-decomposition temperature after aging) / decomposition temperature before aging. The first retention rate is the retention rate of the initial decomposition temperature, and the second retention rate is the retention rate of the maximum weight loss temperature. The test results are shown in Table 2 (unit: %).
[0063] Table 2
[0064]
[0065]
[0066] From the test results of Examples 1-9, it can be seen that the polylactic acid composite material prepared by the preparation method of Examples 10-12 has good aging resistance performance by using the component ratio of the heat-resistant polylactic acid composite material provided by the application.
[0067] From the comparison of the test results of Example 4 and Example 3, it can be seen that the composition of the polyamide and the modification of the carbon fiber can greatly improve the aging resistance performance of the polylactic acid composite material.
[0068] From the comparison of the test results of Example 7 and Example 6, it can be seen that the temperature control in the modification method of the carbon fiber affects the aging resistance performance of the polylactic acid composite material, especially the retention rate of the maximum weight loss temperature.
[0069] From the comparison of the test results of Examples 10-12, it can be seen that the aging resistance performance of the polylactic acid composite material is best after using the preparation parameters provided in Example 12.
[0070] The above is only the preferred embodiment of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A heat-resistant polylactic acid composite, characterized by, By weight parts, including: polylactic acid 80-100 parts, polyamide 66 20-50 parts, carbon fiber 10-30 parts, nano silicon dioxide 5-15 parts; The polylactic acid comprises: 30wt%-40wt% of L-type polylactic acid and the balance of D-type polylactic acid.
2. The heat-resistant polylactic acid composite of claim 1, wherein, The surface of the carbon fiber is grafted with PAMAM.
3. The heat-resistant polylactic acid composite of claim 2, wherein, The mass ratio of PAMAM to carbon fiber is 1:(3-8).
4. The heat-resistant polylactic acid composite of claim 1, wherein, The length of the carbon fiber is 1mm-3mm.
5. The heat-resistant polylactic acid composite of claim 1, wherein, The polyamide comprises: a first component with an average molecular weight of 2000-4000, a second component with an average molecular weight of 6000-8000, and a third component with an average molecular weight of 12000-16000.
6. The heat-resistant polylactic acid composite of claim 5, wherein, The mass ratio of the first component to the second component is 1:(2-4); the mass ratio of the first component to the third component is 3:(5-9).
7. A method for preparing the heat-resistant polylactic acid composite material according to any one of claims 1 to 6, characterized by, Comprising: After melt blending polylactic acid, polyamide 66, carbon fiber and nano silicon dioxide, a heat-resistant polylactic acid composite material is obtained. The blending temperature is 240℃-300℃, and the blending time is 8h-15h.
8. The production method according to claim 7, characterized by, The modification method of the carbon fiber comprises: dissolving PAMAM in a methanol solution, then adding a coupling agent and carbon fiber, reacting at 80℃-240℃ for 5h-8h, and then obtaining modified carbon fiber.
9. The production method according to claim 8, characterized by, After dissolving PAMAM in a methanol solution, a coupling agent and carbon fiber are added, and the temperature is kept at 80℃-120℃ for 1h-3h, then the temperature is raised to 180℃-240℃, and the temperature is kept for 4h-5h, and finally the modified carbon fiber is obtained.
10. The method of claim 9, wherein, The heating rate is 10℃ / min-20℃ / min.